Vimentin S-glutathionylation at Cys328 inhibits filament elongation and induces severing of mature filaments in vitro - Kaus-Drobek, Magdalena; Muecke, Norbert; Szczepanowski, Roman H.; Wedig, Tatjana; Czarnocki-Cieciura, Mariusz; Polakowska, Magdalena; Herrmann, Harald; Wyslouch-Cieszynska, Aleksandra; Dadlez, Michal (Febs Journal, 2020)
Vimentin intermediate filaments are a significant component of the cytoskeleton in cells of mesenchymal origin. In vivo, filaments assemble and disassemble and thus participate in the dynamic processes of the cell. Post-translational modifications (PTMs) such as protein phosphorylation regulate the multiphasic association of vimentin from soluble complexes to insoluble filaments and the reverse processes. The thiol side chain of the single vimentin cysteine at position 328 (Cys328) is a direct target of oxidative modifications inside cells. Here, we used atomic force microscopy, electron microscopy and a novel hydrogen–deuterium exchange mass spectrometry (HDex-MS) procedure to investigate the structural consequences of S-nitrosylation and S-glutathionylation of Cys328 for in vitro oligomerisation of human vimentin. Neither modification affects the lateral association of tetramers to unit-length filaments (ULF). However, S-glutathionylation of Cys328 blocks the longitudinal assembly of ULF into extended filaments. S-nitrosylation of Cys328 does not hinder but slows down the elongation. Likewise, S-glutathionylation of preformed vimentin filaments causes their extensive fragmentation to smaller oligomeric species. Chemical reduction of the S-glutathionylated Cys328 thiols induces reassembly of the small fragments into extended filaments. In conclusion, our in vitro results suggest S-glutathionylation as a candidate PTM for an efficient molecular switch in the dynamic rearrangements of vimentin intermediate filaments, observed in vivo, in response to changes in cellular redox status. Finally, we demonstrate that HDex-MS is a powerful method for probing the kinetics of vimentin filament formation and filament disassembly induced by PTMs.
CRIS-Team Scopus Importer:2020-05-02
Keywords: assembly; cysteine; hydrogen–deuterium exchange mass spectrometry; S-glutathionylation; S-nitrosylation; vimentin